Clostridium difficile in Oncology Patients—Review of Diagnosis and Management in the Indian Setting - Prayag, Parikshit S; Patwardhan, Sampada A; Panchakshari, Shweta P; Prayag, Amrita P (Indian Journal of Medical and Paediatric Oncology, 2023)
Clostridoides (formerly Clostridium) difficile (C. difficile) is a toxin-producing, gram-positive anaerobic bacillus, commonly implicated in antibiotic-associated diarrhea and pseudomembranous colitis. The true burden of C. difficile infection is unclear in India, as it is likely underdiagnosed and underreported. Its incidence is much higher in oncology patients where it can contribute significantly to morbidity and mortality. There are several challenges in the Indian setting, including lack of uniform availability of testing infrastructure, as well as therapy. Oncology patients further present with a unique set of challenges. This article will review the approach to diagnosis and management of C. difficile-associated diarrhea in India, with a focus on oncology patients.
Keywords: Clostridium difficile; gram-positive anaerobic bacillus